2011
DOI: 10.1186/1742-2094-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of Toll-like receptor pathways in traumatically brain-injured mice: effect of exogenous progesterone

Abstract: BackgroundTraumatic brain injury (TBI) causes acute inflammatory responses that result in an enduring cascade of secondary neuronal loss and behavioral impairments. It has been reported that progesterone (PROG) can inhibit the increase of some inflammatory cytokines and inflammation-related factors induced by TBI. Toll-like receptors (TLRs) play a critical role in the induction and regulation of immune/inflammatory responses. Therefore, in the present study, we examined the genomic profiles of TLR-mediated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…Time-course analyses show a peak in C/EBPβ and C/EBPδ mRNA upregulation 24 h after focal cerebral ischemia (Kapadia et al 2006) or traumatic brain injury (Sandhir and Berman 2010). The increase 24 h post-insult has been replicated in many studies (Choi et al 2009;Hua et al 2011;Ridder et al 2009;Tureyen et al 2007;von Gertten et al 2005). Increased C/EBPβ and C/EBPδ mRNA levels have also been reported to occur early in areas of lesion after traumatic brain injury (Oliva et al 2012) or exposure to carbonyl sulphide, a gas that produces highly reproducible neurotoxicity in the rat CNS, particularly in the posterior colliculus (Morrison et al 2009).…”
Section: Ischemic Traumatic or Excitotoxic Injurymentioning
confidence: 88%
“…Time-course analyses show a peak in C/EBPβ and C/EBPδ mRNA upregulation 24 h after focal cerebral ischemia (Kapadia et al 2006) or traumatic brain injury (Sandhir and Berman 2010). The increase 24 h post-insult has been replicated in many studies (Choi et al 2009;Hua et al 2011;Ridder et al 2009;Tureyen et al 2007;von Gertten et al 2005). Increased C/EBPβ and C/EBPδ mRNA levels have also been reported to occur early in areas of lesion after traumatic brain injury (Oliva et al 2012) or exposure to carbonyl sulphide, a gas that produces highly reproducible neurotoxicity in the rat CNS, particularly in the posterior colliculus (Morrison et al 2009).…”
Section: Ischemic Traumatic or Excitotoxic Injurymentioning
confidence: 88%
“…TLR recognition of these endogenous molecules may be involved in the inflammatory response during ''sterile'' tissue damage [10], and the signaling outcomes appear to differ between MAMP-and DAMPinduced TLR activation, which is likely due to the balance requirement between immune intervention and tissue damage repair [25]. Another study using genomic profiles demonstrated that TLR1 was significantly upregulated in traumatically brain-injured mice [26]. In this study, we used an animal model of seizures generated by an intracerebroventricular injection of KA, which is the most popular model of temporal lobe epilepsy and has similar clinical and pathological features to human TLE [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL1B or TNFB, other proinflammatory genes were modulated after the LPS treatment: the CCAAT/ enhancer binding protein (C/EBP), beta (CEBPB) (at 6 dpf), which is known as a key modulator in inflammatory diseases [28][29][30] ; the glutaminyl-peptide cyclotransferase-like (QPCTL) was the most up-modulated gene in the 4-dpf LDexposed fish (fold change of 8.3) and have been reported to be involved in several inflammatory processes, such as Alzheimer's disease 31 or monocyte migration. 32,33 The elevated expression levels of all these molecules explain the exaggerated inflammation response that characterizes septic shock.…”
Section: Sepsis and Tolerance To Lps In Zebrafishmentioning
confidence: 99%